A fast-lock delay-locked loop architecture with improved precharged PFD - Lip-Kai, Soh; Sulaiman, Mohd-Shahiman; Yusoff, Zubaida (SPRINGER, 2008)
In this paper, a dual charge pump architecture for fast-lock delay-locked loop (DLL) is proposed and analyzed. The proposed fast lock DLL uses only one phase frequency detector (PFD) to perform dual path tuning and a lock control circuit to control the switching between the two path. An improved PFD is proposed to reduce the output jitter by reducing the one-shot pulse produced when the reference signal and feedback signal is in phase. The proposed DLL circuit is designed based on the Silterra 0.18-mu m 1P6M CMOS process with a 1.8-V supply voltage. The active area of the proposed DLL circuit is 327.46 x 116.16 mu m. An experimental chip was implemented and measured. The measurement results show that the proposed DLL has fast locking properties.